Quality of Life, Social Support, and Physical Activity of Overweight Adolescents - Suwarsi; Maria Elizabeth Coronel Baua (Journal of Advanced Health Informatics Research, 2023)
Adolescent health and well-being must be at the center of efforts to achieve the Sustainable Development Goals (SDGs) adopted by the World Health Organization in 2030. A solution is needed by first looking at the quality of life of overweight adolescents, their social support, and their physical activity behavior to suggest health interventions for overweight adolescents. This study contributed to test there is a significant difference in the level of involvement in participants' social support and physical activity with the quality of life. The method uses a quantitative, cross-sectional design. The sample is 80 overweight adolescents (13-19 years). The data was measured through a questionnaire tested for validity with a value of 0.9. The sample was selected using the purposive sampling method according to the inclusion criteria and data analysis using frequency and percentage. The result of this study is the majority of overweight adolescents have a low quality of life, good social support, and low physical activity